Collaborative processes in species identification using an internet-based taxonomic resource. Issue 1 (2nd January 2016) - Kontkanen, Jani; Kärkkäinen, Sirpa; Dillon, Patrick; Hartikainen-Ahia, Anu; Åhlberg, Mauri
ABSTRACT: Visual databases are increasingly important resources through which individuals and groups can undertake species identification. This paper reports research on the collaborative processes undertaken by pre-service teacher students when working in small groups to identify birds using an Internet-based taxonomic resource. The student groups are conceptualised as 'knowledge-building communities' working in a 'joint problem space' comprising the collective knowledge of the participants interacting with the taxonomic database. Collaborative group work and associated dialogue were recorded with digital video. The recordings were analysed for the categories of dialogue and the categories of knowledge used by the students as they interacted with the taxonomic database and how they drew on their previous experiences of identifying birds. The outcomes are discussed in the context of the interplay of individual and social processes and the interplay between abstraction and lived experience in the joint problem space.